FoxK1 is Required for Ectodermal Cell Differentiation During Planarian Regeneration - Coronel-Córdoba, Pablo; Molina, M. Dolores; Cardona, Gemma; Fraguas, Susanna; Pascual-Carreras, Eudald; Saló, Emili; Cebrià, Francesc; Adell, Teresa (Frontiers in Cell and Developmental Biology, 2022)
Forkhead box (Fox) genes belong to the ‘winged helix’ transcription factor superfamily. The function of some Fox genes is well known, such as the role of foxO in controlling metabolism and longevity and foxA in controlling differentiation of endodermal tissues. However, the role of some Fox factors is not yet well characterized. Such is the case of FoxK genes, which are mainly studied in mammals and have been implicated in diverse processes including cell proliferation, tissue differentiation and carcinogenesis. Planarians are free-living flatworms, whose importance in biomedical research lies in their regeneration capacity. Planarians possess a wide population of pluripotent adult stem cells, called neoblasts, which allow them to regenerate any body part after injury. In a recent study, we identified three foxK paralogs in the genome of Schmidtea mediterranea. In this study, we demonstrate that foxK1 inhibition prevents regeneration of the ectodermal tissues, including the nervous system and the epidermis. These results correlate with foxK1 expression in neoblasts and in neural progenitors. Although the triggering of wound genes expression, polarity reestablishment and proliferation was not affected after foxK1 silencing, the apoptotic response was decreased. Altogether, these results suggest that foxK1 would be required for differentiation and maintenance of ectodermal tissues.